P16 immunocytochemistry on aspirate smears of neck masses: Another option for determining the HPV status in metastatic head and neck squamous cell carcinoma. Issue 7 (27th June 2019) - Griffith, Christopher C.
Abstract : A recent study has demonstrated the potential for performing p16 immunocytochemistry on routinely collected aspirate smears of metastatic squamous cell carcinoma of the head and neck. In some cases, p16 immunocytochemistry on already collected aspirate smears may be the only available option, so this could be a valuable method that eliminates the need for repeat sampling before clinical staging and management decisions.